Prenatal Monitoring in the Family Health Strategy of the Municipality of Sumé – PB (Research, Society and Development, 2024)
Introduction: Prenatal is the period before the birth of a child, in which a set of actions is applied to the individual and collective health of pregnant women. The Family Health Strategy (ESF) provides quality prenatal care, and the bond established between professionals and pregnant women is essential for their adherence to the Prenatal Assistance Program. This study is important to demonstrate the relevance of prenatal care provided to women by the ESF, contributing to reducing morbidity and mortality related to pregnancy. Objective: To verify prenatal care in the Family Health Strategy of the Municipality of Sumé-PB. Methodology: Quantitative study with a cross-sectional design, having collected data from the SIAB of pregnant women who underwent prenatal care at UBSF, from January to July 2012. Results: 98% were monitored by the ACS; 98% were up to date with their vaccinations; 98% had up-to-date prenatal appointments; 85% started prenatal care in the first trimester and 27% were under 20 years of age. The research was approved by the Research Ethics Committee of the Faculties of Nursing and Medicine Nova Esperança CAAE: 10642612.6.0000.5179. Conclusion: Prenatal care was satisfactory, however, it is necessary for care to be organized in a continuous and systematic manner.